Assessing Knowledge Gaps of Women and Healthcare Providers Concerning Cardiovascular Risk After Hypertensive Disorders of Pregnancy—A Scoping Review - Roth, Heike; LeMarquand, Grace; Henry, Amanda; Homer, Caroline (Frontiers in Cardiovascular Medicine, 2019)
Background: A history of a Hypertensive Disorder of Pregnancy (HDP) at least doubles a woman’s risk of cardiovascular disease (CVD). The risk increases within 10 years after HDP and continues for life, making long-term health after HDP of major public health importance. Understanding knowledge gaps in health care professionals and women regarding cardiovascular health after HDP is an important component in addressing these risks. Objectives: The primary aim was to examine what women and healthcare providers (HCP) know about cardiovascular risks after HDP. The secondary aims were to identify enablers and barriers to knowledge and action on knowledge. Methods: A scoping review was conducted. This was a narrative synthesis, using PRISMA-ScR guidelines, of English-language full text articles that included assessment of knowledge of women, and/or HCPs, on long term cardiovascular risk after HDP. The databases Embase, Medline, Scopus, ProQuest, Cochrane and PsycInfo were searched from 01 January 2005 – 31 May 2019. Results: Twelve studies were included, six addressing women’s knowledge, five addressing HCP knowledge and one addressing both. The studies included 402 women and 1215 HCPs from seven countries. Regarding women’s knowledge, six of seven studies found women had limited or no knowledge about the link between HDP and CVD. Where women were aware of the link, the majority had sourced their own information, rather than obtaining it through their HCP. In five of six studies, HCPs also mostly had limited knowledge about HDP-CVD links. Primary enablers for HCP acquisition of knowledge and counseling were the availability and knowledge of guidelines. Where comparisons between HCP groups were made, obstetricians had greater knowledge than family physicians, internal medical specialists, or midwives. Conclusion: There was a low level of knowledge amongst healthcare providers and women about increased CVD risk after HDP. Where women had higher levels of knowledge, the information was often obtained informally rather than from HCPs. There were variations in knowledge of HCPs, with obstetricians generally more aware than other professions. Further country and context-specific research on current status of women’s and healthcare provider’s knowledge is therefore necessary when creating educational strategies to address knowledge gaps after HDP.